Analysis of the Effect of Employee Service on Customer Satisfaction and WOM Intention at Casual Dining Restaurants in Jakarta - Fitria, Nadya Annisa; Yuliati, Elevita (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
The increase in restaurant numbers every year has affected the intensity of competition in the restaurant industry. To be stand out among competitors, the right perceived image of the restaurant is needed and could be maintained by positive word-of-mouth spread in the community. The present study examines if employee behavior comprising of personal and functional service aspects in casual dining restaurants has an impact on customer satisfaction and word-of-mouth intention at casual dining restaurants. Using a survey approach, the questionnaire was distributed to 198 respondents age 17 years and above, which have already been to one of the particular casual dining restaurants in Jakarta. The data were analyzed using structural equation modeling. Based on the study results, both personal and functional aspects can significantly predict customer satisfaction, although the functional aspects have contributed more considerably than the individual aspects. Besides, the result revealed that customer satisfaction would eventually affect word-of-mouth positively. Limitations and future research directions are also discussed.